Nutrition for health, fitness, & sport - Williams, Melvin H.; Anderson, Dawn E.; Rawson, Eric S. (New York, NY McGraw Hill, 2013)
"This book provides the reader with thorough coverage of the role nutrition plays in enhancing one's health, fitness, and sport performance. Current research and practical activities are incorporated throughout. Major changes in the tenth edition include incorporation of the new Dietary Guidelines for Americans and the associated MyPlate model that has replaced the MyPyramid model. The new MyPlate model, which was designed to be more user-friendly for the American population, is discussed in several chapters. New information from authoritative position statements dealing with exercise and nutrition issues has been incorporated in various chapters where relevant. More than 300 new references, including clinical studies, reviews, and meta-analyses, have also been added to the text." -- Provided by publisher.
Introduction to nutrition for health, fitness, and sports performance -- Healthful nutrition for fitness and sport: the consumer athlete -- Human energy -- Carbohydrates: the main energy food -- Fat: an important energy source during exercise -- Protein: the tissue builder -- Vitamins: the organic regulators -- Minerals the inorganic regulators -- Water, electrolytes, and temperature regulation -- Body weight and composition for health and sport -- Weight maintenance and loss through proper nutrition and exercise -- Weight gaining through proper nutrition and exercise --Food drugs and related supplements.
Includes bibliographical references and index.
Keywords: Nutrition; Physical fitness; Sports -- Physiological aspects